Explicație pas cu pas:
a)
[tex]a = 7 \cdot \frac{1}{2} + 3 \frac{2}{3} = \frac{7}{2} + \frac{11}{3} = \frac{21 + 22}{6} = \bf \frac{43}{6} \\ [/tex]
[tex]b = 4 \times \frac{1}{7} - 3 \times \frac{2}{3} = \frac{4}{7} - \frac{6}{3} = \frac{12 - 42}{21} = \frac{ - 30}{21} = \bf - \frac{10}{7} \\ [/tex]
[tex]E = \frac{1}{3} + a - 2b = \frac{1}{3} + \frac{43}{6} - 2 \cdot \Big( - \frac{10}{7}\Big) = \\ = \frac{ ^{14)} 1}{3} + \frac{^{7)}43}{6} + \frac{^{6)}20}{7} = \frac{14 + 43 \cdot 7 + 20 \cdot 6}{42} \\ = \frac{14 + 301 + 120}{42} = \frac{435}{42} = \bf \frac{145}{14} [/tex]